2014
DOI: 10.1128/jvi.00119-14
|View full text |Cite
|
Sign up to set email alerts
|

Residue 41 of the Eurasian Avian-Like Swine Influenza A Virus Matrix Protein Modulates Virion Filament Length and Efficiency of Contact Transmission

Abstract: Position 41 of the influenza A virus matrix protein encodes a highly conserved alanine in human and avian lineages. Nonetheless, strains of the Eurasian avian-like swine (Easw) lineage contain a change at this position: position 41 of A/swine/Spain/ 53207/04 (H1N1) (SPN04) encodes a proline. To assess the impact of this naturally occurring polymorphism on viral fitness, we utilized reverse genetics to produce recombinant viruses encoding wild-type M1 41P (rSPN04-P) and consensus 41A (rSPN04-A) residues. Relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…The matrix protein forms an inner core of the virion, giving structure and shape to an otherwise pleiomorphic lipid bilayer envelope [ 82 ]. The virus particles can adopt a range of morphologies ranging from rather spherical forms to extended filamentous structures, dictated at least in part by residues in the M1 protein [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Typically, spherical strains are found by electron microscopy in lab-adapted cultures, usually 80–100 nM in diameter, while most natural isolates are filamentous and vary in length [ 84 , 89 , 90 ].…”
Section: Influenza Virus and Host Receptor Interactionsmentioning
confidence: 99%
“…The matrix protein forms an inner core of the virion, giving structure and shape to an otherwise pleiomorphic lipid bilayer envelope [ 82 ]. The virus particles can adopt a range of morphologies ranging from rather spherical forms to extended filamentous structures, dictated at least in part by residues in the M1 protein [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Typically, spherical strains are found by electron microscopy in lab-adapted cultures, usually 80–100 nM in diameter, while most natural isolates are filamentous and vary in length [ 84 , 89 , 90 ].…”
Section: Influenza Virus and Host Receptor Interactionsmentioning
confidence: 99%
“…Previous studies have shown that airborne H7N9 virus transmission can occur, albeit with low efficiency in ferrets 11 12 13 14 , the standard model used to simulate transmissibility among humans 15 . Several viral factors can contribute to the adaptability of avian-like viruses to mammals 16 : virus morphology 17 , receptor-binding specificity 18 , changes in glycosylation patterns of the hemagglutinin (HA) 19 , polymerase activity 20 , the acid stability of the HA 21 and the HA-neuraminidase (NA) balance 22 . Variation in these traits may be controlled by only a few amino-acid substitutions in a virus genome 17 20 21 22 .…”
mentioning
confidence: 99%
“…Several viral factors can contribute to the adaptability of avian-like viruses to mammals 16 : virus morphology 17 , receptor-binding specificity 18 , changes in glycosylation patterns of the hemagglutinin (HA) 19 , polymerase activity 20 , the acid stability of the HA 21 and the HA-neuraminidase (NA) balance 22 . Variation in these traits may be controlled by only a few amino-acid substitutions in a virus genome 17 20 21 22 . Only a few amino-acid changes are required to allow an avian-adapted virus to become airborne-transmissible between mammals, as was demonstrated in the influenza A(H5N1) viruses 23 24 .…”
mentioning
confidence: 99%
“…Mutations in the viral matrix protein of swine influenza A virus have been shown to induce changes in virus shape (39) and to increase virulence in mice (40). Thus, we suggested that the D184N mutation influences the shape of MARV particles and/or the incorporation of the surface glycoprotein GP and explains the increased infectivity of rMARV VP40(D184N) in guinea pig cells compared to that of rMARV WT -infected cells.…”
Section: Discussionmentioning
confidence: 89%